Practical applications for geographic artificial intelligence - سعید, آ.م.د. فوئاد خالید (Sulaimani Journal for Humanities, 2025)
: Artificial intelligence is vast and multifaceted, with diverse methods, techniques, and approaches for problem-solving. The programs and services it provide to geography have led to improved prediction of spatial changes and assistance in all geographic information system analyses, among others. There are many obstacles that prevent the full utilization of this technology. These obstacles include: data availability, data characteristics problems, the lack or absence of researchers' ability to collect and analyze geographic information from different and complex sites, and this is the problem of our research. Therefore, we see that few studies utilize it. The main objective of the research is the ability to practically use artificial intelligence in the field of geography. The researcher relied on the inductive approach and the practical geographic method existing in the field of using modern artificial intelligence techniques. Researchers in our country use geographic artificial intelligence in the methodological field repeatedly, and have not reached deep learning techniques, while research in developed countries has completed practical implementation in geographic fields in most global universities. The research showed that we can use geographic artificial intelligence for geographic research in various fields, most importantly: (creating research title ideas, helping to identify a set of sources relevant to your research or previous research, helping to analyze texts, images, videos, maps, etc.). Most importantly, artificial intelligence helps complete infrastructure that was not easily accessible without artificial intelligence. In this way, we extracted residential neighborhood buildings from the Razkari district from the base map, relying on the mapflow company website and using QGIS software in Sulaymaniyah city as a shapefile for area measurement, and this work is very useful for most geographic research.
Keywords: Artificial Intelligence; Geographic Artificial Intelligence; MAPFLOW Company; QGIS Software; Python Programming